2021
DOI: 10.3389/fbioe.2021.724626
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Reduction of Human Gait for Prosthetic Control

Abstract: We seek to use dimensionality reduction to simplify the difficult task of controlling a lower limb prosthesis. Though many techniques for dimensionality reduction have been described, it is not clear which is the most appropriate for human gait data. In this study, we first compare how Principal Component Analysis (PCA) and an autoencoder on poses (Pose-AE) transform human kinematics data during flat ground and stair walking. Second, we compare the performance of PCA, Pose-AE and a new autoencoder trained on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The selection of input features also is a time-consuming process, and some components of the IMU signals might be found to make little contribution to the prediction precision ( Renani et al, 2021 ). Before the rise of deep learning, some feature engineering methods such as Principal Component Analysis (PCA) remain popular to pre-processing gait data, and then the transformed data were inputted into a regressor/classifier based on a traditional machine learning algorithm such as a Support Vector Machine (SVM) or Decision Tree (DT) ( Boe et al, 2021 ; Lotfi and Kedir-Talha, 2022 ). However, all measurable IMU physical quantities were directly fed into the neural network models in this work, and we rely on the automatic extraction of beneficial intermediate features and abandonment of useless components.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of input features also is a time-consuming process, and some components of the IMU signals might be found to make little contribution to the prediction precision ( Renani et al, 2021 ). Before the rise of deep learning, some feature engineering methods such as Principal Component Analysis (PCA) remain popular to pre-processing gait data, and then the transformed data were inputted into a regressor/classifier based on a traditional machine learning algorithm such as a Support Vector Machine (SVM) or Decision Tree (DT) ( Boe et al, 2021 ; Lotfi and Kedir-Talha, 2022 ). However, all measurable IMU physical quantities were directly fed into the neural network models in this work, and we rely on the automatic extraction of beneficial intermediate features and abandonment of useless components.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis, the biomechanics data were averaged across trials and repetitions of sit-to-stand as PCA suffers from intra-subject correlation and assumes independence of observations. Several studies on the kinematics of human movement comparing linear and nonlinear analytical methodologies have demonstrated that nonlinear methods outperform linear in the percent variance accounted for in the data ( Harbourne et al, 2009 ; Portnova-Fahreeva et al, 2020 ; Boe et al, 2021 ). Furthermore, if the variables are linearly related, then PCA and NLPCA both result in the same solution.…”
Section: Methodsmentioning
confidence: 99%
“…However, apart from the output layer, the symmetric form Hinton and Salakhutdinov (2006) of the autoencoder is used, where the decoder consists of a mirror network to the encoder. This encoder has previously been shown proven to extract useful latent representations for lower-limb activities Boe et al (2021) and hand movements Portnova-Fahreeva et al (2020 , 2022) .…”
Section: Methodsmentioning
confidence: 99%